Aortoesophageal fistula in a patient with carcinoma of the esophagus - Case report - Queiroz de Sousa, Gonçalo (2016)
Primary aortoesophgeal fistulas (AEF) are a rare but life-threatening condition because of substantial hemorrhage, requiring fast treatment to ensure patient survival. We report a case of a 69-year-old male with diagnosis of squamous cell carcinoma of the esophagus who suffered an episode of hematemesis and hemorrhagic shock. Gastrointestinal (GI) endoscopy revealed an ulcerated lesion with pulsatile hemorrhage. CT-scan confirmed the diagnosis of AEF. A stent-graft was placed in the descending aorta to control bleeding, and 2 days later an esophageal stent was deployed to reduce risk of aortic graft infection. The patient was discharged 13 days after admission and had no other episode of GI bleeding in a 6-month follow-up period. TEVAR may be used as a palliative or bridge treatment of AEF.